INVESTIGATE CRISIS MANAGEMENT OF MONEY CHANGER INDUSTRY DURING COVID-19 PANDEMIC - Ni Putu Sri Utami Dewi; Gede Sri Darma (Jurnal Ekonomi, 2022)
The COVID-19 pandemic has delivered uncertainty and shocks to money changers as one of growing industry in Bali’s tourism sector due to decrease in banknotes transaction obtained from foreign tourist. This study explores the challenges faced by money changers and the strategies used to survive. Using interpretive phenomenological approach, semi-structured interviews were conducted with 10 owners, directors, and managers of money changers in Bali. The findings show that various challenges faced during pandemic, including psychological, decreased turnover and transaction volume, daily rate volatility, stock management, temporary branch closures, and transformed human resource practices. Strategies used to survive the crisis, such as creating crisis team, managing capital structure and cash availability, banknotes stock management system, renewing employee contracts, marketing strategies to reach local segment, and comply with health protocols. The development of digital-based foreign exchange platform post pandemic which might be disrupt money changer industry are also discussed as future research.